Challenges and support for parents of children with autism spectrum disorder at work - Laili, Nurdiyana; Wan Abdullah, Wan Arnidawati; Toran, Hasnah; Amin, Aizan Sofia; Alias, Roslinda (Human Resource Management Academic Research Society, 2021)
Generally, there is a public awareness that parents of children with autism syndrome disorder (ASD) face significant challenges in raising their children. This research aims to investigate the challenges and problems faced by these parents in the workplace. A qualitative study with purposive sampling was implemented. Three informants (N=3) were recruited from a family support group and went through an in-depth interview twice using a semi-structured format. The data were recorded, transcribed and analysed using thematic analysis. Among themes that emerged from the data were lack of exposure to ASD, peer views on parents of children with ASD, employer's concern for these parents, and cooperation between co-workers and parents of children with ASD. This study provides ideas and views for both employers and employees in Malaysia who deal with parents of children with ASD to guide workplace support and pull-down obstacles for these parents. This study is hoped to help the community, government agencies, and non-governmental organisations continue to pay attention to and assist parents of children with ASD in the workplace in order to raise awareness about ASD and encourage parents of children with ASD to continue working without worrying about childcare.